Social Innovation in the context of Strategic Knowledge Management Processes for Supply Chain Performance Enhancement - Muhamad Nizam Jali; Zakaria Abas; Ahmad Shabudin Ariffin (International Journal of Supply Chain Management, 2017)
The current knowledge-innovation led economy has regards social innovation and strategic knowledge management processes as a vital combination in addressing social, economic and technological problems in a concurrent way. Strategic knowledge management processes that consist the process of knowledge creation, knowledge transfer and knowledge application creates superior knowledge resource that can be embedded into products, processes and services which makes them highly innovative and ultimately contributes towards improving social well-being, enhance economic growth and also improving technological aspect. In similar vein, supply chain management is an integrated system and network which involves the connection process of supplier-end user relationship in terms of producing and delivering of a product, processes and services to the end users. The various network integration processes within the supply chain management system involves different background and motives of actors which may exposed the system into risks that perhaps may disrupt and affect the supply chain performance. Thus, this paper explores and gives a useful insight on the contribution of superior knowledge resource created within the processes of strategic knowledge management among actors in the supply chain management network. The new superior knowledge resource works as a vital solution to enhance the performance process of supply chain management network by improving external integration with suppliers, external integration with customers, and supply chain risk and therefore, helps to improving the quality of peoples life, stimulate economic growth and enhance technological advances i.e. social innovation.